Closing the Gap: Genetic and Genomic Continuum from Syndromic to Nonsyndromic Craniosynostoses - Heuzé, Yann (Curr Genet Med Rep, 2014)
Craniosynostosis, a condition that includes the premature fusion of one or multiple cranial sutures, is a relatively common birth defect in humans and the second most common craniofacial anomaly after orofacial clefts. There is a significant clinical variation among different sutural synostoses as well as significant variation within any given single-suture synostosis. Craniosynostosis can be isolated (i.e., nonsyndromic) or occurs as part of a genetic syndrome (e.g., Crouzon, Pfeiffer, Apert, Muenke, and Saethre-Chotzen syndromes). Approximately 85 % of all cases of craniosynostosis are nonsyndromic. Several recent genomic discoveries are elucidating the genetic basis for nonsyndromic cases and implicate the newly identified genes in signaling pathways previously found in syndromic craniosynostosis. Published epidemiologic and phenotypic studies clearly demonstrate that nonsyndromic craniosynostosis is a complex and heterogeneous condition supporting a strong genetic component accompanied by environmental factors that contribute to the pathogenetic network of this birth defect. Large population, rather than single-clinic or hospital-based studies is required with phenotypically homogeneous subsets of patients to further understand the complex genetic, maternal, environmental, and stochastic factors contributing to nonsyndromic craniosynostosis. Learning about these variables is a key in formulating the basis of multidisciplinary and lifelong care for patients with these conditions.